2021
DOI: 10.7717/peerj.12657
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal spine disposition and pelvic tilt during outdoor fitness equipment use and their associations with kinanthropometry proportions in middle-aged and older adults

Abstract: Background Outdoor fitness training has become popular as a tool for improving the health, especially middle-aged and older adults. For this purpose, outdoor fitness equipment (OFE) have been installed in public areas. However, their safety and effectiveness are still unknown. The aim of the present research was to analyze the sagittal disposition of the spine and pelvic tilt during the use of OFE, and to determine the influence of anthropometric variables on these factors in middle-aged and old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…OFE manufacturing companies should redesign equipment to allow users to regulate and adjust the equipment to their own anthropometric characteristics. (Abelleira-Lamela et al, 2021; Chow et al, 2017; McGill et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OFE manufacturing companies should redesign equipment to allow users to regulate and adjust the equipment to their own anthropometric characteristics. (Abelleira-Lamela et al, 2021; Chow et al, 2017; McGill et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Attention should also be paid to spinal errors. Another study that analyzed other OFE devices and their information panels also found that, in exercises in which participants were standing, significant misalignments were made in the spine, increasing the risk of future injury (Abelleira-Lamela et al, 2021). There are numerous mistake patterns associated with the spine because it functions as a unitary structure (Panjabi, 1992).…”
Section: Discussionmentioning
confidence: 99%